Work stress and coping among professionals - Chan, Kwok B. (Social sciences in Asia, 2007)
While aspiring to escape from the drudgery and alienation which seem to be the fate of manual workers, professionals have long realized to their distress that their professionalism and work commitment by no means reduce the stressfulness of their work. Such an awareness of the impact of work on their physical and emotional well-being has led the professionals to make efforts to maximize their person-environment fit and to enhance their coping and adaptation, knowing, sometimes helplessly, that society, bureaucracy, and work organization continue to be a potent source of work stress. This book offers deep analyses of work stress and coping among professionals by a multidisciplinary research team of sociologists, psychologists, psychiatrists, social workers, and human resources experts. The work lives of seven groups of professionals are profiled and compared in this book: doctors, lawyers, engineers, nurses, teachers, police officers, and life insurance agents. Based on a large-scale survey, in-depth interviews, and comparative analyses, this book suggests practical recommendations and policy measures for personal, organizational as well as societal intervention. Work stress is a social problem - as such it requires a societal solution. Meanwhile, individual professionals cope and adapt in the way they know best, which is certainly not a satisfactory response.